The Study of Copper Alloy with Graphene Additive via x-Ray Diffraction - Masri, M.N.; Mohammad, M.; Yusoff, M.; Mamat, S.; Teo, P.T.; Othman, R.; Irfan, A.R.; Singh, Pramod K. (Archives of Metallurgy and Materials, 2022)
This study evaluated the effect of milling speed and compaction pressure on the densification and morphology of the CuZn-Gr composite. The composite was prepared by using the powder metallurgy technique. The effect on the microstructural and compaction was determined based on different milling speeds. The different milling speeds involved were 175, 200, 225, and 250 rpm. Meanwhile, the different compaction pressures used in this study were 127, 250, 374, and 500 MPa. The properties of the milled powder gave the result to green density and densification parameters. The XRD pattern of Cu and Zn broadened as milling time increased.
Keywords: Copper Alloy; Graphene; powder metallurgy; Copper; zinc